(untitled) (Experimental biology, 2015)
Soil depletion and degradation reduces the productivity of cultivated crops and plant resistance to rugged environmental conditions. One of the ways of restoring soil fertility is mycorrhiza. Studies have shown that co-inoculation of Claroideoglomus and Rhizophagus genera mycorrhizal fungi with suspensions of Anabaena laxa (Rabenh.) A. Br. blue-green algae profoundly increases the effect of mycorrhization, eliciting a significant augmentation of chlorophyll and carotinoid concentration in leaves of Avena sativa L. The results, obtained in the course of this experiment, can be used in development of relevant technologies both for agriculture, in order to increase crop yield and soil fertility of arable land and pastures, and ecology - for remediation and restoration of anthropogenically deteriorated land.